Criminology Analysis On Paedophiles In The City Of Gorontalo - Kiat Alwi Ismail (Universitas Negeri Gorontalo, 2019)
The purpose of this study is to know and analyze to find out and analyze criminology reviews of pedophile offenders in the city of Gorontalo and to find out to analyze the form of legal protection against pedophilia in the city of Gorontalo. Based on understanding the types of research and looking at the problems behind the writing of this scientific work, the research used is empirical juridical. The approach taken by the author is in the form of an interview is a form of data collection technique that is widely used in observation. The interview technique conducted by the author is oral at a meeting with the source (respondent) to get information and documentary studies are away or style in the system of collecting data by combining and analyzing documents either in writing, drawing or electronically. Data analysis is carried out searches and compiled in a direct and contained manner from the results of interviews, records in the field, and other materials so that it can be understood easily, and obtained can be informed to others. Based on the results of the analysis of pedophile cases over the past 4 years that this case was declared to have been fingerprinted by investigators before being disbursed due to obstacles during the trial process so that from the last 4 years some cases are still in the process of fingerprinting or there has been no verdict.